1986
DOI: 10.1007/bf00915380
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in human leukocyte function induced by ingestion of eicosapentaenoic acid

Abstract: Two groups of six adults with persistent asthma, who were identical clinically, received 0.1 or 4 g of purified eicosapentaenoic acid ethyl ester (EPA) daily for 8 weeks. Both doses increased significantly the generation of leukotriene B5 (LTB5) from EPA by polymorphonuclear (PMN) and mononuclear leukocytes, while only the high dose decreased leukocyte arachidonic acid (AA) and the generation of LTB4 and prostaglandin E2 from AA. Only the high dose led to inhibition of PMN leukocyte chemotaxis to multiple stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2

Year Published

1988
1988
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(67 citation statements)
references
References 24 publications
8
57
2
Order By: Relevance
“…Consuming fish oil results in partial replacement of AA in inflammatory cell membranes by EPA (Lee et al, 1985;Endres et al, 1989) and thus demonstrates a potentially beneficial anti-inflammatory effect of n-3 PUFA. Supplementing the diet with n-3 PUFA has been shown to reduce AA concentrations in neutrophils and neutrophil chemotaxis, reduce LT generation (Lee et al, 1985;Payan et al, 1986), and reduce airway late response to allergen exposure (Arm et al, 1989). These data are consistent with the proposed pathway by which dietary intake of n-3 PUFA modulates lung disease.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Consuming fish oil results in partial replacement of AA in inflammatory cell membranes by EPA (Lee et al, 1985;Endres et al, 1989) and thus demonstrates a potentially beneficial anti-inflammatory effect of n-3 PUFA. Supplementing the diet with n-3 PUFA has been shown to reduce AA concentrations in neutrophils and neutrophil chemotaxis, reduce LT generation (Lee et al, 1985;Payan et al, 1986), and reduce airway late response to allergen exposure (Arm et al, 1989). These data are consistent with the proposed pathway by which dietary intake of n-3 PUFA modulates lung disease.…”
Section: Introductionsupporting
confidence: 70%
“…Okamoto et al (2000a, b) observed suppression of LTB 4 and LTC 4 generation by leukocytes and improvement in respiratory function following 4 weeks of perilla seed oil (n-3 PUFA)-rich supplementation in asthmatic subjects. Payan et al (1986) found that high doses, compared to low doses, of EPA ethyl ester taken daily for 8 weeks increased LTB 5 generation, and reduced AA, LTB 4 , and PGE 2 generation by polymorphonuclear (PMN) and mononuclear leukocytes in asthmatic patients. These authors did not report pulmonary function scores, medication use, or asthma symptom scores.…”
Section: Interventional Studiesmentioning
confidence: 99%
“…We have previously wrestled with the issue of an ideal control fatty acid to compare with fish oil (5) and in this investigation, chose corn oil, having used olive oil in 2 previous studies (5,ll). It is not unlikely that there are some mono-or polyunsaturated fatty acids that have potentially significant immunologic effects (24)(25)(26)(27). We believe that the issue of the ideal placebo dietary intervention to compare with fish oil has not yet been settled.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a number of studies have been conducted investigating the possible therapeutic affects of fish oil on asthmatic adult patients. It has been reported that fish oil supplementation in patients with asthma has antiinflammatory effects [264][265][266] . Also, fish oil trials have shown beneficial effects on asthma clinical outcomes 267 .…”
Section: Immune System Disordersmentioning
confidence: 99%